Two-photon absorption and cell imaging of two multi-branched dyes based on curcumin. (December 2015) - Xu, Guoyong; Wang, Jiafeng; Si, Guifu; Wang, Mahong; Wu, Baoxing; Zhou, Shuangsheng
Abstract: Two novel multibranched dyes curcumin-based: 1, 7-bis(4′-propyloxy-3′-methyloxy-phenyl)-3-propyloxy-5-carbonyl-1, 6-heptadiene (dye 1 ) and 1, 7-bis(4′-acetate ethyloxy-3′-methyloxy-phenyl)-1, 6-heptadiene-4, 4-diacetate ethyl-3, 5-dione (dye 2 ) were easily prepared. Their one- and two-photon absorption properties have been investigated carefully. The two-photon absorption (TPA) cross sections measured by two-photon excited fluorescence (TPEF) were determined to be 1143 and 842 GM fordye 1 anddye 2, respectively. Cell viability tests revealed the as-prepared compounds possessed low cytotoxicity against MCF-7 cell lines over a period of at least 24 h. In addition, in vitro and in vivo studies demonstrated thedye 1 could enter into tumor cells, and even rapid accumulate in tumor tissues, which makes it an ideal organic material for biomedical imaging. Graphical abstract: Two novel multi-branched dyes based on curcumin had been synthesized. The experimental results show that the as-prepared compounds bear low toxicity, strong TPEF and large TPA cross-section, which has been used potentially for biological two-photon fluorescent probe. Highlights: Two multi-branched dyes based on curcumin are synthesized. The obtained compounds exhibited large TPA cross-section. The obtained compounds have low toxicities. The dye 1 could used potentially as biological probe. The dye 1 could accumulated rapidly in tumor tissues.